Specific in vitro interferon-gamma and IL-2 production as biomarkers during treatment of chronic Q fever - Schoffelen, Teske; Wegdam-Blans, Marjolijn C.; Ammerdorffer, Anne; Pronk, Marjolijn J. H.; Soethoudt, Yvonne E. P.; Netea, Mihai G.; van der Meer, Jos W. M.; Bleeker-Rovers, Chantal P.; van Deuren, Marcel (Frontiers in Microbiology, 2015)
Background: Antibiotic treatment of chronic Q fever is cumbersome and of long duration. To monitor treatment, there is a the need for alternative biomarkers. C. burnetii-specific interferon (IFN)-γ and interleukin (IL)-2 production reflect the type of effector and memory T-cell response. In chronic Q fever, C. burnetii-specific IFN-γ production is higher and IL-2 production is lower than in individuals with past Q fever. Here we explore whether C. burnetii-specific IFN-γ and IL-2 production correlate to treatment response. Methods: We studied the longitudinal C. burnetii-specific IFN-γ/IL-2 ratio in fifteen proven chronic Q fever patients. All patients were followed for at least 18 months during antibiotic treatment. Treatment was considered successful when clinical recovery was observed, a positive PCR for C. burnetii DNA in blood became persistently negative, anti-phase I IgG showed a fourfold decrease or more, and imaging techniques showed disappearance of infectious foci. Results: Overall, the IFN-γ/IL-2 ratio declined when patients experienced a successful treatment outcome. When treatment failed, IFN-γ/IL-2 ratios did not significantly decrease. The median(±IQR) slope of the longitudinal IFN-γ/IL-2 ratio with successful treatment was -2.10 (-7.02 to -0.06), and -0.15 (-1.13 to 0.25) with unsuccessful treatment (P=0.19). Q fever endocarditis patients had higher IFN-γ/IL-2 ratios than patients with endovascular infections. Conclusions: We propose that the IFN-γ/IL-2 ratio can be used as an additional biomarker for monitoring chronic Q fever treatment, with declining ratios being indicative of successful treatment.